The 'Omics' of Voluntary Exercise: Systems Approaches to a Complex Phenotype. (December 2015) - Kelly, Scott A.; Villena, Fernando Pardo-Manuel de; Pomp, Daniel
Abstract : Predisposition to engage in exercise is highly variable and simultaneously influenced by the environment, complex genomics, and their interactions. Given the importance of exercise to health, understanding the underlying influences of variability is crucial. Here, we discuss murine systems approaches, focusing on 'omics', relevant to revealing the architecture of voluntary activity.